Sosialisasi Peraturan Pemerintah no 71 Tahun 2000 Dalam Mewujudkan Jiwa Sadar Hukum dan Sikap Anti Korupsi Kepada Siswa dan Siswi Kelas XI SMAN 34 Jakarta - Edward Benedictus Roring; Hannatrie Syalsabillah; Amanda Mutiara Natasya; Fadia Fatimatuzzahra; Subakdi Subakdi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The urgency in several cases of student delinquency stems from law breaking attitudes and corruption cases which are increasingly common in our country, Indonesia. This occurs due to the dysfunction of several law enforcement agencies which are considered not to have emphasized their function in educating and anticipating cases of law violations in society. Some basic examples of legal awareness education and anti-corruption attitudes carried out in schools are students practicing through the honesty canteen, students practicing remembering their own assignments/exercises, students practicing identifying honest characters, schools providing special extracurriculars. So that way students and teachers understand the benefits of honesty and discipline. However, it should be noted that legal awareness education and an anti-corruption attitude should not be provided at elementary school level alone, this education must continue at subsequent educational levels because at the same time educational institutions at the upper level can be a strong milestone and reminder for building accountability and transparency.